Induction of tumor lymphangiogenesis by VEGF-C promotes breast cancer metastasis - Skobe, Mihaela; Hawighorst, Thomas; Jackson, David G.; Prevo, Remko; Janes, Lauren; Velasco, Paula; Riccardi, Lucia; Alitalo, Kari; Claffey, Kevin; Detmar, Michael (Nature medicine, 2001)
Metastasis of breast cancer occurs primarily through the lymphatic system, and the extent of lymph node involvement is a key prognostic factor for the disease. Whereas the significance of angiogenesis for tumor progression has been well documented, the ability of tumor cells to induce the growth of lymphatic vessels (lymphangiogenesis) and the presence of intratumoral lymphatic vessels have been controversial. Using a novel marker for lymphatic endothelium, LYVE-1, we demonstrate here the occurrence of intratumoral lymphangiogenesis within human breast cancers after orthotopic transplantation onto nude mice. Vascular endothelial growth factor (VEGF)-C overexpression in breast cancer cells potently increased intratumoral lymphangiogenesis, resulting in significantly enhanced metastasis to regional lymph nodes and to lungs. The degree of tumor lymphangiogenesis was highly correlated with the extent of lymph node and lung metastases. These results establish the occurrence and biological significance of intratumoral lymphangiogenesis in breast cancer and identify VEGF-C as a molecular link between tumor lymphangiogenesis and metastasis.